SPÓŁDZIELNIA A KONCEPCJE NEOINSTYTUCJONALNE - Ławrynowicz, Jan (Wydział Prawa i Administracji UAM, 2004)
The article evaluates the usefulness of agency theory and property rights and Williamson’s transaction cost economics as a framework for discussing five major problems o f cooperatives. Property rights held by cooperative owners and delegation of decision-making authority from principal to agent impose a significant level o f conflict to the decision-making process, particularly involving the allocation o f resources. As a result o f this inherent conflict, the traditional cooperative exhibits five basic problems: free rider problem, horizon problem, portfolio problem, control problem and influence cost problem. This article also examines how these problems are overcome by New Generation Cooperatives.
COOPERATIVE AND THE NEOINSTITUTIONALISTS THEORIES